The impact of exchange rate deviations from relative PPP equilibrium on the U.S. demand for foreign equities. (October 2017) - Grossmann, Axel; Paul, Chris; Simpson, Marc W.
Highlights: Impact of US dollar stages and foreign equity securities purchased by US residents. The sample contains data from 22 developed and 25 developing countries. FX stages are important when analyzing US allocations to foreign equities. We find a negative relationship between undervalued US dollar and foreign equities. The findings suggest the wealth effect and the profit-oriented effect can coexist. Abstract: Applying fixed-effects panel data, this study investigates the impact of U.S. dollar exchange rate movements during different exchange rate states (overvaluation and undervaluation) on the monthly real gross and real net purchases of foreign equities by U.S. residents over the post-Plaza Accord period. The foreign equities come from 22 developed and 25 developing countries. Previous research has posited two alternative hypotheses regarding the relationship between exchange rates and foreign investment. These are the wealth effect and the profit-oriented effect. The evidence herein suggests that these two hypotheses coexist. We find robust evidence for a negative relationship between the exchange rate movements of an undervalued U.S. dollar and the demand for foreign equities. For developed countries, the wealth effect dominates the profit-oriented effect when the U.S. dollar is overvalued, while, for developing countries, the profit-oriented effect dominates the wealth effect. The results emphasize the importance of considering exchange rate states derived from a relative PPP equilibrium when analyzing U.S. allocations to foreign equities. The findings with respect to the macroeconomic control variables are mainly in agreement with the predictions of international financial theory. Some of the results, however, disappear or become inconclusive for the period after the bankruptcy of Lehman Brothers. This may be explained by the increased uncertainty in international financial markets following this unprecedented event. The findings are robust with respect to different constructed equilibrium exchange rates.